Festival Trademark Market: Proses Pembentukan Modal Sosial Pasar Industri Kreatif Lokal di Kota Bandung - Audia Pramesti (Umbara, 2018)
This study discusses social capital mapping on local fashion creative industries and fashion festival in Trademark Market festival in Bandung. This study views Trademark Market festival as a social domain rather than merely economy domain which consists of social capitals that is worked for the concern of creative economy. Trademark Market festival played its role as a venue for local brands to do selling, branding, and social networking with other parties. This study applied qualitative method, in particularly ethnography. The data collection technique included observation, interviews, literature study, and documentation. The data is presented chronologically; pre-, during, and after the-festival. The study suggests three types of social capital building being the fashion festival: (1) bonding relationship that is sharing session among local creative industry actors, independent festival that is held by local brands, coveying information about fashion festival among tenants, and using friend’s merit as a catalog model, (2) bridging relationship, can be seen repeated orders by customer due to ‘Loyal to Customer’ vision, privilege for local brands to be accepted as tenant on curation process, and (3) linking relationship, can be seen on the recruitment of booth keeper by tenants and festival crew, by the trust of tenant candidates due to the luxuriousness of the festival, and also wholesale buy-and-sell transaction with the third party.